2020
DOI: 10.1128/mra.01025-20
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Caulobacter crescentus Operon Annotation Based on Transcriptome Data

Abstract: Caulobacter crescentus is a model alphaproteobacterium with a well-studied genetic network controlling its cell cycle. Essential for such studies is an accurate map of the expressed features of its genome. Here, we provide an updated map of the expressed RNAs by integrative analysis of 5′ global rapid amplification of cDNA ends, transcriptome sequencing, rifampicin treatment RNA sequencing, and RNA end-enriched sequencing data sets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…As expected, we observed significant peak within the hfiA promoter region (Figure 4A). Peaks were highly enriched near globally defined transcription start sites (TSS) [30-32] when compared to a set of randomly generated peaks (Figure 4B); this TSS-proximal enrichment pattern is characteristic of proteins that directly bind DNA to regulate gene expression. To identify putative binding motifs in the ChIP-seq peaks, we analyzed the peak sequences using the XSTREME algorithm within the MEME Suite [33].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As expected, we observed significant peak within the hfiA promoter region (Figure 4A). Peaks were highly enriched near globally defined transcription start sites (TSS) [30-32] when compared to a set of randomly generated peaks (Figure 4B); this TSS-proximal enrichment pattern is characteristic of proteins that directly bind DNA to regulate gene expression. To identify putative binding motifs in the ChIP-seq peaks, we analyzed the peak sequences using the XSTREME algorithm within the MEME Suite [33].…”
Section: Resultsmentioning
confidence: 99%
“…The Bioconductor package was used to identify overlap between RtrC-regulated genes defined by RNA-seq and RtrC binding sites defined by ChIP-seq [61]. Promoters for genes were designated as the sequence -400 to +100 around the TSS [30]. Overlap between promoters and RtrC motifs identified from XSTREME was analyzed using ChIPpeakAnno within Bioconductor.…”
Section: Rna-seq and Chip-seq Overlap Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial transcriptome architecture maps provide an ideal platform to analyze TIR accessibility on a transcriptome-wide scale. Notably, transcription start site (TSS) data and RNA-seq density data have been used previously to experimentally map bacterial transcriptomes (33). If such TSS data are available, the user can input this together with the genbank file of the respective genome containing the CDS annotations and an operon map to build a transcript architecture model that allows the best starting point for transcriptome analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Further genome wide analysis revealed that SD sites are also prevalent within the coding sequence where they may induce ribosome pausing and are predicted to be non-functional for initiation (8)(9)(10), although neither has been thoroughly tested. The bacterium C. crescentus is the fastest growing species that is predominantly nonSD in translation initiation and it also has a well annotated transcriptome (11,12), making it an ideal model to probe how mRNA sequence features program translation initiation in TIRs as opposed to AUGs in the CDS (called elongator AUG regions henceforth) in predominantly nonSD species.…”
Section: Introductionmentioning
confidence: 99%